Knowledge and Perception of Family/friends Towards Visiting Time in Intensive Care Unit at Queen Elizabeth Central Hospital - Mapira, Madalitso (Kamuzu University of Health Sciences, 2022)
This is a qualitative study which aimed at exploring the knowledge, and perceptions of family/friends towards visiting time in Intensive Care Unit at Queen Elizabeth Central Hospital. A sample of ten family members/friends was randomly selected and interviewed individually using an interview guide. The data collected was then analyzed manually using content analysis. The study found that most family members/ friends have some knowledge of the importance of restricting visitors in ICU. However, despite the fact that much is known on importance of restricting visiting hours in ICU, the study found that family and friends were not happy with the current visiting time. The main concern was on the actual period of 30 minutes, which they viewed as not enough for all the visitors. Majority of the respondents suggested extending visiting time to an hour or two. However, the findings of this study may not be generalized because of a small sample size